Designing an Agent-Based Model for a City-Level Simulation of COVID-19 Spread in Cyprus - Fayad, Philip; Hadjipetrou, Stylianos; Leventis, Georgios; Kavroudakis, Dimitris; Kyriakidis, Phaedon (My University, 2023)
To date, several epidemiological agent-based models have been developed to study the spread of the highly infectious coronavirus (SARS-COV) disease in different countries. However, no extensive effort has been implemented for the Republic of Cyprus. In this research, we present the design framework of the EPIMO-LCA agent-based model that respects the SEIR epidemiological model and attempts to simulate human mobility to predict the spread of COVID-19 at a city-level of detail. More specifically, we fully describe the three main model components (agents, environment and interactions) and explain all anticipated functionalities, processes, input and output elements. The agent-based model envisaged is expected to contribute to a better understanding of the interactions between intervention measures and disease spread for the city of Larnaca, the Republic of Cyprus, and beyond.
Keywords: Agent-Based Models; COVID-19; Spatial Simulation; Cyprus